Penerapan Metode Fuzzy Logic Pada Tempat Pemberi Pakan Kucing Menggunakan Sensor HC-SR04 - Rima Tamara Aldisa; Puspa Ayu Soleha (STMIK Budi Darma, 2022)
This tool can help in feeding cats using the HC-SR04 Sensor. The author designed the application of the Fuzzy Logic Method to the Cat Feeder Using the HC-SR04 Sensor by making this tool useful as a feeder for cats. A tool is made that is expected to control or give food portions so that they do not experience a lack of food with a fairly good portion by applying the Fuzzy Logic method to control the distance for cats with the tool every day. If the feed provided has been used up by the cat, if the cat moves closer to the feed, the tool will automatically open. Automatic system by utilizing the HC-SR04 sensor, if the cat gets close to the feed it will automatically open with a range of 3 meters if it exceeds it will not open